Linguistic Alternation in Libyan Arabic: A Sociolinguistic Examination of Code-switching - Abdulhady, Saad (International Journal of Language and Literary Studies, 2024)
This study investigates the prevalence and functions of code-switching (CS) among non-Arabic-speaking educators at the University of Benghazi, with particular emphasis on how CS impacts identity formation and fosters a sense of belonging within the community. A sociolinguistic approach was adopted in the study, utilizing qualitative semi-structured interviews with a purposively selected sample to elicit in-depth insights into the types and functions of CS. Findings reveal that tag-switching is significantly more prevalent than inter-sentential code-switching, which improves social cohesiveness and interaction in bilingual settings. Participants strategically employed code-switching to create an inclusive learning environment, aligning with existing literature on the role of language choice in fostering student engagement. Furthermore, CS facilitates pragmatic functions, such as reducing tension and clarifying requests, while bridging language barriers with individuals of varying English proficiency. This article simply highlights CS as a significant social strategy that improves the educational process and fortifies cultural identification, suggesting its potential to be promoted inclusively in bilingual settings. The long-term impacts of code-switching on social integration and academic performance should be investigated in future research.